Comparative Approaches to Studying Strategy: Towards an Evolutionary Account of Primate Decision Making - Sarah F. Brosnan; Michael J. Beran; Audrey E. Parrish; Sara A. Price; Bart J. Wilson (Evolutionary Psychology, 2013)
How do primates, humans included, deal with novel problems that arise in interactions with other group members? Despite much research regarding how animals and humans solve social problems, few studies have utilized comparable procedures, outcomes, or measures across different species. Thus, it is difficult to piece together the evolution of decision making, including the roots from which human economic decision making emerged. Recently, a comparative body of decision making research has emerged, relying largely on the methodology of experimental economics in order to address these questions in a cross-species fashion. Experimental economics is an ideal method of inquiry for this approach. It is a well-developed method for distilling complex decision making involving multiple conspecifics whose decisions are contingent upon one another into a series of simple decision choices. This allows these decisions to be compared across species and contexts. In particular, our group has used this approach to investigate coordination in New World monkeys, Old World monkeys, and great apes (including humans), using identical methods. We find that in some cases there are remarkable continuities of outcome, as when some pairs in all species solved a coordination game, the Assurance game. On the other hand, we also find that these similarities in outcomes are likely driven by differences in underlying cognitive mechanisms. New World monkeys required exogenous information about their partners' choices in order to solve the task, indicating that they were using a matching strategy. Old World monkeys, on the other hand, solved the task without exogenous cues, leading to investigations into what mechanisms may be underpinning their responses (e.g., reward maximization, strategy formation, etc.). Great apes showed a strong experience effect, with cognitively enriched apes following what appears to be a strategy. Finally, humans were able to solve the task with or without exogenous cues. However, when given the chance to do so, they incorporated an additional mechanism unavailable to the other primates - language - to coordinate outcomes with their partner. We discuss how these results inform not only comparative psychology, but also evolutionary psychology, as they provide an understanding of the evolution of human economic behavior, and the evolution of decision making more broadly.